Biocomposites from Thermoplastic Postindustrial Waste Starches Filled with Mineral Fillers for Single‐Use Flexible Packaging. Issue 6 (7th April 2022) - Scharnowski, Jenna B.; Rodriguez‐Uribe, Arturo; Pal, Akhilesh K.; Wang, Tao; Snowdon, Michael R.; Misra, Manjusri; Mohanty, Amar K.
Abstract: Plasticized starch (PS) materials hold a fundamental role in the design of novel biodegradable and compostable plastics aimed to reduce global single‐use plastic wastes. This work exemplifies the plasticization of postindustrial waste wheat starch (pWWS) and postindustrial corn starch (pWCS) with a comparison to food‐grade corn starch (pCS) by introducing technical waste glycerol (25%) along with urea (5%) and water. The PS (30%) is blended with 70% poly(butylene adipate‐ co ‐terephthalate) (PBAT) to design a matrix with optimized mechanical properties. As a result, the inclusion of pWCS and pCS shows similar impact strength and melt flow index (MFI) values. Further, the mineral fillers, i.e., talc and calcium carbonate (CaCO3 ) (25%), are introduced into the PBAT/PS (70%/30%) matrix to explore the effect on MFI, mechanical, thermal, and morphological properties. Scanning electron microscopy analysis reveals good dispersion of PS particles and mineral fillers into the PBAT. Adding talc into the PBAT/pWWS and PBAT/pCS blends shows significantly higher modulus (≈134% and ≈105%, respectively) and heat deflection temperature (HDT) (7.8% and 9.3%, respectively). The addition of 25% CaCO3 results in the impact strength of PBAT/pWWS being improved by ≈20%. Due to talc's lamellar platelet structure and better dispersion, the inclusion of talc into the PBAT/PS blends shows improved rheological properties compared to that of CaCO3 . Abstract : Postindustrial starches are successfully plasticized with glycerol, urea, and water and incorporated as thermoplastic starches into poly(butylene‐ co ‐adipate terephthalate). The produced TPS shows good comparability to those containing food‐grade starch. The addition of talc filler into the TPS results in better dispersion in the matrix and overall composite performance than those filled with calcium carbonate.